Be Careful How You Treat Your Coworkers: The Reciprocal Relationship between Ethnic Outgroup Coworkers' Reactions to Voice and Ethnic Majority Employees' Attitudes regarding Immigrant Entitlements. Issue 3 (2nd November 2022) - Stanojevic, Antonia; Akkerman, Agnes; Manevska, Katerina
Abstract: We study the reciprocal relationship between interethnic interactions among coworkers and native (Dutch) employees' attitudes regarding immigrant entitlements. Building on contact theory, we hypothesize that voice support by ethnic outgroup coworkers leads to more favorable, while voice suppression leads to less favorable attitudes regarding immigrant entitlements. Furthermore, we examine potential reciprocal effects. The hypotheses are tested using a three-wave panel survey of native Dutch respondents. Findings indicate a negative effect of voice suppression by ethnic outgroup coworkers on attitudes regarding immigrant entitlements, implying that workplace interethnic contact can shape political attitudes. Moreover, findings indicate that the less favorable native employees' attitudes regarding immigrant entitlements are, the more likely they are to subsequently experience suppression by ethnic outgroup coworkers.